Effect of intermittent teriparatide (PTH 1-34) on the alveolar healing process in orchiectomized rats - de Oliveira, Danila [UNESP]; de Oliveira Puttini, Igor [UNESP]; Silva Gomes-Ferreira, Pedro Henrique [UNESP]; Palin, Letícia Pitol [UNESP]; Matsumoto, Mariza Akemi [UNESP]; Okamoto, Roberta [UNESP] (Springer Nature, 2019)
Objective: To evaluate intermittent teriparatide therapy’s influence on the alveolar healing process in rats with induced osteoporosis. Materials and methods: Fifty-four male rats were divided into three groups: fictitious surgery (SHAM), bilateral orchiectomy (ORQ NT), and bilateral orchiectomy treated with teriparatide (ORQ TERI). Right upper incisor extraction was performed. After 14 and 42 days, the rats were euthanized. Immunolabeling analysis was performed in order to characterize bone turnover through Wnt, alcaline phosphatase, osteocalcin, and TRAP presence in tissue; micro-CT analysis was performed in order to determine the bone volume fraction (BV/TV), trabecular thickness, separation, and number (Tb.Th, Tb.Sp, Tb.N). For the micro-CT data, statistical analysis was performed through one-way ANOVA and Tukey post-test, for parametrical data, with significance level adopted in p < 0.05. Days, Wnt, alkaline phosphatase, and osteocalcin revealed more labeling for ORQ TERI and less for TRAP. For the Tb.N in the ORQ NT group was 0.496 mm, a significant statistical difference was observed between the groups of ORQ NT and ORQ TERI (p < 0.05). For the BV/TV, Tb.Sp, and Tb.Th parameters, no significant statistical difference was observed among the three experimental groups (p > 0.05). Conclusions: Treatment with intermittent teriparatide reverted impairment in the metabolism of repairing bone tissue in orchiectomized animals. Clinical relevance: Cases of decreased bone density such as osteoporosis can lead to delayed alveolar repair process. PTH 1-34 has been shown to be a medication that improves this repair, making bone of low quality into one with normal features.
Keywords: Alkaline phosphatase; Men; Orchiectomy; Osteoporosis; Teriparatide; Wnt proteins